2012
DOI: 10.3201/eid1804.111415
|View full text |Cite
|
Sign up to set email alerts
|

Cosavirus Infection in Persons with and without Gastroenteritis, Brazil

Abstract: To determine possible cosavirus association with clinical disease, we used real-time reverse transcription PCR to test children and HIV-positive adults in Brazil with and without gastroenteritis. Thirteen (3.6%) of 359 children with gastroenteritis tested positive, as did 69 (33.8%) of 204 controls. Low prevalence, frequent viral co-infections, and low fecal cosavirus RNA concentrations argue against human pathogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 13 publications
4
34
2
Order By: Relevance
“…Only on the basis of statistical analysis on clinical manifestation of cosavirus and its co-infection, we can conclude its significant association with gastroenteritis. Our data only supports the previous studies reported association of cosavirus in gastroenteritis from other countries 16,[28][29][30][31][32][33] . Previously cosavirus was only reported in stool samples of patient suspected for the acute flaccid paralysis (AFP) in India 34 .…”
Section: Table 3: Comparison Of Quantitative Clinical Parameters Betwsupporting
confidence: 50%
See 2 more Smart Citations
“…Only on the basis of statistical analysis on clinical manifestation of cosavirus and its co-infection, we can conclude its significant association with gastroenteritis. Our data only supports the previous studies reported association of cosavirus in gastroenteritis from other countries 16,[28][29][30][31][32][33] . Previously cosavirus was only reported in stool samples of patient suspected for the acute flaccid paralysis (AFP) in India 34 .…”
Section: Table 3: Comparison Of Quantitative Clinical Parameters Betwsupporting
confidence: 50%
“…In 2012 Stocker et al reported presence for the cosavirus in Patients with gastroenteritis as well as in control group 30 . Very low prevalence (0.01% to 3.6%) of cosavirus was reported from other countries like in Japan, Thailand and Brazil 28,30,33 . In this study we found 3% prevalence of cosavirus.…”
Section: Table 3: Comparison Of Quantitative Clinical Parameters Betwmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of HCoSV genomes was first examined by TaqMan-based qPCR [11], using a LightCycler Ò 480 RealTime PCR Instrument II (Roche Diagnostics, Mannheim, Germany). The genome copy numbers of HCoSV were determined based on a standard curve prepared with tenfold serial dilutions of plasmid DNA containing the partial 5' UTR sequence of strain HCoSV-A1 (GenBank accession number: J438902).…”
Section: Introductionmentioning
confidence: 99%
“…Human Enterovirus type C has also been identified among healthy children [32,33]. Human Cosavirus (for the common stool-associated Picornavirus) and human Salivirus (for the stool Aichi-like virus), which are not yet recognized as new species, have been reported in several studies in stool samples from healthy children [5,34,35,36,37,38]; however, an understanding of their pathogenicity is lacking because they can also be present in cases of gastroenteritis.…”
Section: Exploring the Viral Flora In Humansmentioning
confidence: 99%